Die ökonomische Bewertung der Feldberegnung unter Berücksichtigung von Risiko und veränderter Wasserentnahmeerlaubnisse; The Economic Valuation of Irrigation under Consideration of Risk and Changes in Water Withdrawal Permits - Ulla Kellner; Oliver Mußhoff; Henning W. Battermann (German Journal of Agricultural Economics (GJAE), 2012)
– The European Union has established the Water Framework Directive (WFD) as a legal framework to protect all aquatic ecological systems including groundwater. This directive is primarily aiming at water protection and may have advantages for the water regime in sensitive areas. Nevertheless, it may also involve economic disadvantages for agricultural enterprises. In this paper we analyze the economic implications of the WFD for farmers using irrigation, i.e., the negative economic consequences for farms resulting from a reduction of water withdrawal permits in the north-east of Lower Saxony. In a whole farm risk programming approach we show how much benefit farmers loose if the amount of water withdrawal permits is reduced. To avoid solutions that would possibly exceed the farmers' risk tolerance, the apparently accepted standard deviation of the program's total gross margin is used as an upper bound in the optimization. This should represent an observable reflection of the individual risk attitude of the farmers. The results demonstrate that deterministic approaches do not consider all economic impacts caused by the reduction of water withdrawal permits as well as that risk has to be considered.
Keywords: 330